Low carbohydrate diet to achieve weight loss and improve HbA1c in type 2 diabetes and pre‐diabetes: experience from one general practice. (March 2014) - Unwin, David; Unwin, Jen
Abstract: Patients with diabetes have long been exhorted to give up sugar, encouraged instead to take in fuel as complex carbohydrate such as the starch found in bread, rice or pasta (especially if 'wholemeal'). However, bread has a higher glycaemic index than table sugar itself. There are no essential nutrients in starchy foods and people with diabetes struggle to deal with the glycaemic load they bring. The authors question why carbohydrate need form a major part of the diet at all. The central goal of achieving substantial weight loss has tended to be overlooked. The current pilot study explores the results of a low carbohydrate diet for a case series of 19 type 2 diabetes and pre‐diabetes patients over an eight‐month period in a suburban general practice. A low carbohydrate diet was observed to bring about major benefits. Blood glucose control improved (HbA1c 51±14 to 40±4mmol/mol; p<0.001). By the end of the study period only two patients remained with an abnormal HbA1c (>42mmol/mol); even these two had seen an average drop of 23.9mmol/mol. Weight fell from 100.2±16.4 to 91.0±17.1kg (p<0.0001), and waist circumference decreased from 120.2±9.6 to 105.6±11.5cm (p<0.0001). Simultaneously, blood pressure improved (systolic 148±17 to 133±15mmHg, p<0.005; and diastolic 91±8 to 83±11mmHg, p<0.05). Serum gamma‐glutamyltransferase decreased from 75.2±54.7 to 40.6±29.2 U/L (p<0.005). Total serum cholesterol decreased from 5.5±1.0 to 4.7±1.2mmol/L (p<0.01). This approach is easy to implement in general practice, and brings rapid weight loss and improvement in HbA1c . Copyright © 2014 John Wiley & Sons. Practical Diabetes 2014; 31(2): 76–79